Genetic and Environmental Risk Factors for Isolated Hemangiomas in Infants - Anna Materna-Kiryluk; Katarzyna Wiśniewska; Barbara Więckowska; Katarzyna Wróblewska-Seniuk; Beata Jaroszewska-Świątek; Ewa Helwich; Anna Latos-Bieleńska (MDPI AG, 2020)
The goal of this analysis is to identify risk factors for infantile hemangiomas (IH) to better delineate hemangioma predisposition. We analyzed live birth children with isolated cutaneous hemangioma that were reported to the Polish Registry of Congenital Malformations from across Poland between the years 1998 and 2016. Lower birthweight and gestational age were the most significant risk factors associated with IH. We also observed a trend for a higher risk of IH with a lower level of maternal and paternal education. Moreover, mothers with IH have a higher probability of having a child with IH compared to fathers. However, this association is only present when the child is female. Similarly, a higher risk of hemangioma in a female child is found among mothers having relatives of the first degree with IH, compared to fathers with a similar pedigree. Our results suggest the role of exogenous factors in the etiology of IH. The analysis of familial cases suggests a multifactorial model of inheritance. The study indicates that female gender is an important risk factor for the expression of familial IH. Potential interaction of genetic risk factors with exposure to female sex hormones may play a role in the development of IH.